2008
DOI: 10.1007/s10096-008-0489-3
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic frontiers: preventing and treating infectious diseases by inhibiting bacterial quorum sensing

Abstract: Density-dependent cell-cell communication, or quorum sensing (QS), has been demonstrated in numerous species of bacteria. The basic function of QS is likely to confer a nutritional advantage, particularly in a highly populated, mixed-species environment. QS also has ramifications on the production of colonization and virulence factors. Pheromone-like substances secreted into the extracellular milieu appear to govern many of the transcription products in these bacteria. At a high cell density, the QS systems ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 55 publications
0
40
0
Order By: Relevance
“…Fatty acid metabolism in especially complex in pseudomonads, with an unusually large genetic allocation to both the catabolism and anabolism of fatty acids (32,50,51). To further confirm the two activities of PA3286 observed in P. aeruginosa PAO1, to probe the substrate specificity and to determine whether PA3286 requires partner proteins for intercepting ␤-oxidation cycle intermediates, we introduced the PA3286 gene into the model E. coli strain BW25113.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatty acid metabolism in especially complex in pseudomonads, with an unusually large genetic allocation to both the catabolism and anabolism of fatty acids (32,50,51). To further confirm the two activities of PA3286 observed in P. aeruginosa PAO1, to probe the substrate specificity and to determine whether PA3286 requires partner proteins for intercepting ␤-oxidation cycle intermediates, we introduced the PA3286 gene into the model E. coli strain BW25113.…”
Section: Figmentioning
confidence: 99%
“…syringae B728a (black); PFLU, P. fluorescens SBW25 (black); Avin, Azotobacter vinelandii DJ (purple); b, E. coli (green). tion of iron acquisition by blocking siderophore production (53), and QS inhibition in particular (50), have garnered substantial interest as strategies for treating P. aeruginosa infections. The three dominant QS signal molecules from the las, rhl, and PQS systems, all of which contain fatty acid moieties, together form a complex, cell density-dependent regulatory circuit controlling the expression of a suite of virulence factors (87,89).…”
Section: Figmentioning
confidence: 99%
“…Furthermore, it has been shown that the interruption of bacterial communication by quorum quenching can prevent pathogens from displaying virulent behavior (7). Therefore, quorum quenching could be used in the development of new antimicrobial strategies because many pathogens depend on quorum sensing in regulating virulence (6,8).…”
mentioning
confidence: 99%
“…It appears there may be that more than one compound present in the ginseng extract, one of which is an agonist of swarming, with others that may affect a different signalling pathway in Pseudomonas aeruginosa PAO1, stimulating pyocyanin synthesis. Indeed, major pathogens such as P. aeruginosa, have evolved with numerous QS circuits, which modulate the production of various toxins and regulate parallel QS systems (Martin et al, 2008). Swarming motility in itself is a complex phenotype that involves several other traits (Overhage et …”
Section: Resultsmentioning
confidence: 99%